Consumerism Culture of Urban Communities Based on Islamic Economic Perspective - Hanif Hanif; Is Susanto (Agregat: Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study is to analyze the consumerism culture of urban communities based on the Islamic economic perspective. This research is a descriptive study with a qualitative approach, which uses data reduction, data display, and concluding. The data collection methods were divided into two types, the library method, and the field method. The love of property is being experienced by some urban communities in the city of Bandar Lampung. According to the results of research and studies conducted by the writers, consumption can be defined as the use of goods or services to meet all human needs. The level of consumption that occurs in urban communities in Bandar Lampung can be defined as tahsiniyah, hajiyah, dharuriyah, and hajiyah. The consumerism culture has flourished in the majority of Bandar Lampung citizens.